Blockchain Technology in Healthcare System for Sharing Confidential Information between Departments and Doctors - Pundlik , Manish; Jadhav , Pramod Pandurang (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In healthcare industry for managing private and confidential information Personal Health Record (PHR) management systems are a popular solution. These systems are mainly offering the solution of managing the access control. The implementation complexity and maintenance cost make it expensive to maintain the PHR system. The employment of Blockchain technology in order to manage access of data, which is needed to be share between multiple users, may improve the cost of implementation and running resources. Additionally, it also helps to maintain privacy, security, audit-ability, and tracking. In this paper, Blockchain-based privacy preserving data sharing system has been proposed. The aim of the proposed system is to maintaining the data access control between different doctors and departments. The system contains two parts first part contains the user definition and the personalized access rules. The second part includes the utilization of definitions and applies during the data access. The prototype of the model has been implemented and the performance of the system has been measured. The results demonstrate the efficiency and low resource consumption of the proposed privacy preserving data sharing system.